KAJIAN DESAIN PENANGANAN OPRIT JEMBATAN (STUDI KASUS: JEMBATAN DESA PIHANIN KABUPATEN HULU SUNGAI SELATAN PROVINSI KALIMANTAN SELATAN) - Markawie Markawie (Jurnal Teknologi Berkelanjutan, 2020)
The landslide on the Pihanin Bridge oprit towards Pihanin Village resulted in the interruption of land transportation routes and it was deemed necessary to repair. The landslide on the oprite was caused by the inability of the subgrade, which is relatively soft to support the Laterite embankment load as high as 4.5 m, with a specific gravity of 1.85 ton/m3 . The methodology used in handling the oprit is collecting secondary data in the form of road/bridge geometric data, soil investigation data (CPT/Sondir test and N-SPT test), soil data analysis, landslide analysis using GeoStudio 2012 software to estimate the landslide area with trial parameters. soil, so that sf < 1 is obtained which can be considered as a landslide field and the representative soil parameters are the same as those in the field. The next step is to calculate the load that refers to the SNI 1725:2016. From the results of the analysis, the design for handling landslides on the Pihanin bridge using box culvert type triple reinforcement with dimensions of length p = 8 m; width l = 10.2 m ; height t = 1.75 m, supported by 18 x 18 cm2 square piles, 12 m long. Analysis of the external stability of the slide shows the safety factor SF = 0.999 without reinforcement (existing condition) and SF = 2.622 with reinforcement (final condition). From the calculation of the forces acting on the pile in the form of an axial amount of 141.99 kN, with an allowable axial force capacity of 181.66 kN, while the lateral force that occurs is 4.96 kN with an allowable lateral force capacity of 216 kN.